Strategi Pembelajaran Aktif Dengan Media Puzzle Untuk Meningkatkan Pemahaman Siswa Terhadap Siklus Makhluk Hidup - Tey, Kristianti; Ali, Aisyah; Rusli, Tiffany Shahnaz (Jurnal Riset Pendidikan Dasar (JRPD), 2025)
This study aims to evaluate the effectiveness of puzzle-based learning media in improving students' understanding of the life cycle. The research method used was classroom action research (PTK) consisting of two cycles. The subjects of this study were 30 students of class 3C of SD Negeri Inpres Yotefa. Data were collected through learning outcome tests, observation of student activeness and interviews with teachers. Data analysis was done descriptively and quantitatively. The results showed that the use of puzzle media contributed positively to students' understanding. In the pre-cycle, only 40% of students reached the KKM (â‰¥75). After the intervention in cycle 1, the percentage of completeness increased to 57.2%, and in cycle 2 it increased again to 60.7%. This increase indicates that puzzle-based learning helps students understand the concept of the life cycle better than conventional methods. This study provides implications that puzzle media can be an innovative alternative in science learning in elementary schools, especially for conceptual materials.